HUBUNGAN SIKAP REMAJA TERHADAP PERILAKU SEKS BEBAS DENGAN TINGKAT PENALARAN MORAL PADA SISWA KELAS DUA DI SMA NEGERI 1 GUNUNG MERIAH KABUPATEN ACEH SINGKIL - Muhammad Syakir Marzuki; Mutiara Zelika Azri NST (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Adolescents are residents in the age range of 10-18 years. Adolescence is a period of transition from children to adults. This period is a period of preparation for adulthood which will pass through several important developmental stages in life.Â There are two factors that can influence behavior in adolescents, namely internal factors and external factors. Moral development is a development related to the rules and norms regarding what humans should do both in their interactions with other people. This research is analytical research with analytical descriptive approach. Â This research was conducted by distributing questionnaires in the form of a google form to second grade students at SMA Negeri 1 Gunung Meriah Aceh Singkil who met the sample criteria with research indicators 1 = strongly disagree, 2 = disagree, 3 = agree, 4 = strongly agree. After the data were analyzed, it was found that the attitude of adolescents towards free sex was good 44 (36.7%), enough 70 (58.3%), less than 6 (5.0%). Adolescents who have poor moral reasoning are 6 (100%), quite good 7 (61.4%), good 44 (36.7%). A chi-square test was performed and the value (Pvalue = 0.001) which means that there is a relationship between Adolescent Attitudes Against Free Sex Behavior and the Level of Moral Reasoning at SMA Negeri 1 Gunung Meriah Aceh Singkil.Keywords: Adolescent Attitude, Free Sex Behavior, Adolescent Moral Reasoning